HRM policies' impact on employees' employability: The role of age climate and the offering of developmental measures - Marlene Schrimpf; Dominik Emanuel Froehlich; Barbara Covarrubias Venegas (Administrative Sciences, 2021)
How can (aging) individual employees continue to grow as persons, on the one hand, and contribute to their employing organizations in meaningful ways, on the other hand? In this article, we set out to study how two important instruments of human resource management - age climate and the offering of developmental measures - may help. We use path modeling to investigate the research model based on data of 208 respondents of both rural and urban regions in Austria. The results indicate that a positive organizational age climate has a positive influence on the offering of developmental measures and, subsequently, on employees' employability. We emphasize the importance of facilitating developmental measures for staff of all ages, as well as the necessity to address the organizational age climate to successfully tackle the challenges of demographic change.
Keywords: 350; age; age climate; competences; employability; human resource development